GE_GERICHTE C/17366/2014 vom 6. März 2017 - GE Cour de justice (2017)
BAIL À LOYER ; CONTESTATION DU CONGÉ ; LOCAL PROFESSIONNEL ; PROLONGATION DU BAIL À LOYER | LOY.89; CO.253; CO.271; CO.272; CO.272b;